2017
DOI: 10.12788/jhm.2820
|View full text |Cite
|
Sign up to set email alerts
|

Blood Products Provided to Patients Receiving Futile Critical Care

Abstract: The number of hospitalized patients receiving treatment perceived to be futile is not insignificant. Blood products are valuable resources that are donated to help others in need. We aimed to quantify the amount of blood transfused into patients who were receiving treatment that the critical care physician treating them perceived to be futile. During a 3-month period, critical care physicians in 5 adult intensive care units completed a daily questionnaire to identify patients perceived as receiving futile trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The proportion of inappropriate patients in this study was 11.4% of all included patients, in line with the proportion of several studies conducted in the United States and Europe that reported 10.4% and 14% of patients as futile, respectively [13,14]. However, studies conducted in the United States including over 1,000 patients reported that 11% of patients were perceived by physicians as receiving futile treatment and 8.6% were perceived as receiving probably futile treatment, which is higher than our study [1,4,5]. Another study in the United States reported 20.9% of patients were perceived by physicians as receiving futile treatment, which is also a higher proportion than the current study [15].…”
Section: Discussionsupporting
confidence: 84%
“…The proportion of inappropriate patients in this study was 11.4% of all included patients, in line with the proportion of several studies conducted in the United States and Europe that reported 10.4% and 14% of patients as futile, respectively [13,14]. However, studies conducted in the United States including over 1,000 patients reported that 11% of patients were perceived by physicians as receiving futile treatment and 8.6% were perceived as receiving probably futile treatment, which is higher than our study [1,4,5]. Another study in the United States reported 20.9% of patients were perceived by physicians as receiving futile treatment, which is also a higher proportion than the current study [15].…”
Section: Discussionsupporting
confidence: 84%
“…As a result, there is significant concern regarding blood product use for patients with futile outcomes. 12 Since a large percentage of all massive transfusion protocols (MTPs) occur in the setting of trauma, it stands to reason that the reduction in waste would be greatest by adjustments made in the trauma environment. 13 While there is agreement in the surgical community that MTP should be terminated for futile resuscitation, there are no specific guidelines or biomarkers to assist in this decision.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, there is significant concern regarding blood product use for patients with futile outcomes. 12…”
Section: Discussionmentioning
confidence: 99%